2021
DOI: 10.1021/acsomega.0c05096
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Pharmacological Characterization of Ascorbic Acid and Nicotinamide Chitosan Nanoparticles against Insulin-Resistance-Induced Cognitive Defects: A Comparative Study

Abstract: High consumption of industrialized food with high fat content is generally associated with insulin resistance, which in turn causes memory impairment and cognitive decline. Nicotinamide and ascorbic acid are among the promising neuroprotective molecules; however, an appreciable therapeutic activity necessitates the administration of a large dose of either. Therefore, the study aimed to assess if loading them in chitosan nanoparticles in doses 5–10 times lower than the unencapsulated forms would achieve compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…In addition, it was previously reported that 8-hydroxy-2-deoxyguanosine (8OHdG); which is a repair product of oxidized guanine lesions, is directly connected to elevated oxidative stress or disease states, and could be used as a reliable marker of cellular DNA damage and repair [ 50 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was previously reported that 8-hydroxy-2-deoxyguanosine (8OHdG); which is a repair product of oxidized guanine lesions, is directly connected to elevated oxidative stress or disease states, and could be used as a reliable marker of cellular DNA damage and repair [ 50 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first group of rats ( n = 10) were fed a standard control diet and tap water, serving as the normal control group. The other groups were administered HFHF diet for seventy‐five days (Abd‐Allah et al, 2020b, 2021) On the 60th day, insulin resistance (IR) was confirmed by measuring fasting glucose and insulin, and computing the fasting insulin sensitivity indices. Afterwards, treatments were supplemented orally for two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Other mechanisms are also compromised in WD-induced cognitive damage: insulin (INS) signaling in the brain [ 60 , 68 ], blood-brain barrier (BBB) permeability [ 41 , 57 , 62 ], HPC inflammation [ 45 , 46 , 49 , 54 , 60 , 68 ], microglia activation [ 54 , 57 , 65 , 68 , 72 ], endoplasmic reticulum (ER) and oxidative stress [ 43 , 51 , 58 , 60 , 61 , 71 ], gut microbiome composition [ 44 , 46 , 54 , 56 , 58 ], and neurogenesis [ 59 ]. Therapeutic strategies based on modulating these mechanisms have demonstrated unequal effects on memory loss.…”
Section: Western Dietmentioning
confidence: 99%